2010
DOI: 10.1111/j.1759-6831.2010.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling confusions in inflorescence morphology: Patterns and diversity of reproductive shoot ramification in angiosperms

Abstract: Terminology of inflorescence diversity has often been used in a confusing way in the literature, partly because it was based on uncritical and outdated definitions. In particular, the terms cyme, thyrse, and panicle have been misused. Although a more critical classification worked out by several authors is available, it is unfortunately not in general use because most of the relevant publications are written in German. In addition, some terms have not been used in the same way by morphologists and developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
167
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 126 publications
(144 reference statements)
4
167
1
9
Order By: Relevance
“…Because female inflorescences are unknown, we score inflorescence type (42) based on the male structures, which we interpret as spikes of unistaminate flowers (as did Friis et al 2006Friis et al , 2011, but inflorescence partial units (43) as unknown, because the female flowers may or may not have been borne in cymose units, as in Hedyosmum (which has male spikes and female thyrses, both included in the same state of character 42). Contrary to earlier authors (Endress 1987;Todzia 1988;Eklund et al 2004;Endress and Doyle 2009), Doria et al (2012) interpreted the partial units in female inflorescences of Hedyosmum as spikes, rather than monochasial cymes. Under this hypothesis, the total number of bracts within and subtending each unit should be one more than the number of flowers.…”
Section: Chloranthaceae and Possible Relativescontrasting
confidence: 61%
See 4 more Smart Citations
“…Because female inflorescences are unknown, we score inflorescence type (42) based on the male structures, which we interpret as spikes of unistaminate flowers (as did Friis et al 2006Friis et al , 2011, but inflorescence partial units (43) as unknown, because the female flowers may or may not have been borne in cymose units, as in Hedyosmum (which has male spikes and female thyrses, both included in the same state of character 42). Contrary to earlier authors (Endress 1987;Todzia 1988;Eklund et al 2004;Endress and Doyle 2009), Doria et al (2012) interpreted the partial units in female inflorescences of Hedyosmum as spikes, rather than monochasial cymes. Under this hypothesis, the total number of bracts within and subtending each unit should be one more than the number of flowers.…”
Section: Chloranthaceae and Possible Relativescontrasting
confidence: 61%
“…Friis et al (2001) interpreted all floral parts as whorled, but on more critical examination Friis et al (2009) were unable to detect either orthostichies or clockwise and counterclockwise parastichies that are inclined at different angles, which would indicate whorled or spiral phyllotaxis, respectively (Endress 2006;Endress and Doyle 2007). Based on these observations and the absence of Fibonacci numbers, they concluded that phyllotaxis was probably not spiral, but whorled phyllotaxis could not be established either.…”
Section: Nymphaealesmentioning
confidence: 95%
See 3 more Smart Citations